Peran Pemerintah dalam Upaya Penanganan Permasalahan Gelandangan dan Pengemis di Kota Jakarta - Bintang, Cantika Ramadhani; Komeni, Wirdi Hisroh; Azhari, Rizka Anugrah; Bustani, Simona (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
In Indonesia in urban centers, vagrants and beggars are a concern for the government. This role is the implementation of the 4th paragraph related to social welfare. The government has directly played a role and is directly involved in handling the problem of vagrants and beggars. Various ways have been done including by using Government Regulation Number 31 of 1980, but these efforts have not been able to produce results. The study of what the author describes provides the latest alternative solution as an effort to overcome and provide a feasible solution by the homeless beggars, namely by providing skills, education, and religious teachings in order to be able to bring them to a better direction. After the problem has been resolved, the second is to strengthen the legal substance, namely by regulating clear and more specific rules, After the substance has been regulated, the most appropriate alternative and solution is to record how many homeless people are in the center of the Capital City, after that they are given temporary placement by those who do not have a clear home, and see who is not physically strong to be treated and given skills when they are healthy later, and for those who are still healthy, they are given decent work skills with skills according to the fields they want. The last is to provide residential placement and the budget will be funded by the APBD for this, data is collected and calculated who deserves the placement and sees the eligibility of homeless people and beggars who are entitled to occupy it.